PRODUKSI DAN KUALITAS LATEKS KARET (Hevea brasilliensis Muell. Arg) KLON PB 260 PADA PENYADAPAN KE ATAS DAN KE BAWAH - Rudi Hartawan; Nasamsir Nasamsir; Marjohan Marjohan; Edy Marwan (Universitas Batanghari, 2020)
This study aims to determine the effect of rubber tapping type on the results and quality of PB 260 clone latex. The design of this study uses complete random desingn, consisting of 2 treatments, namely T1 treatment (down ward tapping type) and T2 treatment (Type up ward tapping). Each treatment was repeated 3 times so that the number of experimental plots was 6 plots. Where the treatment is placed randomly in plots and blocks as replications. For each plot of the experiment consists of 10 plants, so that the total number of plants is 60 plants. The results of research show that the lower tapping type gives more results but the quality of latex is not different from the type of tapping up.